Social Media and Political Preferences Among Generation Z in the 2024 Indonesian General Election - Kusumawardani, Vidya; Sheila Silvia Permatasari; Chandra Agustin, Dinar Ayu (Fakultas Usluhuddin dan Dakwah UIN Syekh Wasil Kediri, 2025)
Social media and politics are inextricably intertwined variables. In a democratic system, social media has proven to be a valuable tool for political engagement. This study investigates the relationship between social media and political preferences among Generation Z in the context of the 2024 Indonesian Presidential Election. A total of 41 undergraduate students from the Faculty of Economics, Business, and Social Sciences at Universitas 17 Agustus 1945 Jakarta participated in an online survey conducted via Google Forms from April to May 2024. The survey targeted students aged 17–22 years from various academic disciplines. The questionnaire was structured into three thematic categories: